RE-POLITICIZING RACE IN COMMUNITY DEVELOPMENT: USING POSTCOLONIAL PSYCHOLOGY AND PHOTOVOICE METHODS FOR SOCIAL CHANGE - Kessi, Shose (PINS-Psychology in Society, 2025)
How far can community development lead to transformative social change within the context of global north-south development agendas? Drawing on the works of Frantz Fanon and Steve Biko, this article explores the possibilities of postcolonial psychology for community-based change. Findings from a youth intervention based on Photovoice methods and involving 51 young people from four urban communities in Sub-Saharan Africa reveal that racial identity, self-determination, and social inequality remain key concerns. The paper discusses the advantages and limitations of postcolonial psychology for mobilising communities towards change and the role of participatory action research methods such as Photovoice for marginalised communities to gain widespread recognition and promote transformative action in a globalised context.